Geomechanical characterization of carbonates of the Sete Lagoas Formation (Bambuí Group) - Ilambwetsi,Archange Michael (2020)
Abstract The geomechanical properties of rock masses must be identified to assess their quality and employability; however, the methodologies may differ depending on the lithotype and analytical purposes. The present study aimed to estimate the not-well-known physical-mechanical properties of three types of carbonate rocks (calcarenite, calcilutite, and marble) of Sete Lagoas Formation, which are not recognized in scientific literature, southeast Brazil. These are important rocks from an economic point of view, as they comprise an important input for cement, fertilizers and construction material. Both physical indexes (apparent porosity, apparently dry and saturated specific mass, apparent absorption capacity and wave propagation velocity) and mechanical properties (uniaxial compression, point load and slake durability) were determined. Mechanical tests for these three rock types were correlated to those of other carbonate rocks from other countries, for comparisons. The results showed that the lithotypes under study are peculiar in terms of porosity, wave propagation velocity and strength. Also found were a very high durability and a very good correlation between specific mass and uniaxial compressive strength.